Digital photography an introduction - Ang, Tom (2018)
This comprehensive photography companion shows you everything you need to do to start taking exquisite photographs with digital cameras and phones. Beginning with core techniques every photographer needs to master, this updated edition of Digital Photography: An Introduction progresses through a series of 15 projects that encourage you to practice and refine your skills. Quick troubleshooting tips help you fix common image problems, including those related to distortion, color, detail, and backgrounds. Tom Ang also gives expert advice for developing, editing, organizing, adjusting, cropping, and printing images, while an accompanying buying guide helps you choose the right camera, lenses, lighting, accessories, computers, and printers.
"Content previously published in Digital Photographer's Handbook."
S. Sanchez (Recommending faculty) AY 2022-2023
Includes index.
Keywords: Photography -- Digital techniques; Image processing -- Digital techniques; Digital cameras -- Handbooks, manuals, etc